Pengaruh Brand Image dan Brand Trust terhadap Loyalitas Pengguna Smartphone Samsung di Kota Medan: Penelitian - Joyce Alicia Agatha Munthe; Onan Marakali Siregar; Kartini Harahap (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this study is to evaluate the impact of brand image and brand trust on consumer loyalty of Samsung smartphones in Medan City. This study aims to provide deeper insight into how these two aspects influence consumer preferences. The influence of these two variables will be examined both individually and simultaneously on user loyalty. The methodology used in this study adopts a quantitative approach with a survey design. Data were obtained by distributing questionnaires to Samsung smartphone users in Medan City face-to-face and through the Google Form online form. Data processing was carried out using statistical methods to test the hypothesis regarding the relationship between brand image and brand trust on customer loyalty. The results of the study indicate a strong relationship between these variables. The correlation coefficient (R) value of 0.746 shows this. In addition, the Adjusted R Square value of 0.548 indicates that 54.8% of the variation in loyalty can be explained by brand image and brand trust. Most respondents showed a good perception of Samsung's brand reputation, which then influenced their purchasing decisions and loyalty to the brand.